Contra la posibilidad del vacío: el argumento mecanicista de Leibniz - Brown, Gregory (2014)
Discussion of an argument that Leibniz formulated against the existence of empty space in any possible world, even when space is conceived to be relational. This argument is based on the idea that each substance, and indeed each body, must express, by some natural means, all the other bodies in its world.